IMPLEMENTATION OF HAPPY AND PROSPEROUS FAMILY NORMAL FAMILY WITH HISTORICAL LEARNING DIFFICULTY IN STUDENTS CLASS VIII SEMESTER II M.Ts AT STATE 1 BANYUWANGI - Purnia Astutik (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2020)
The family has the primary role and responsibility for the care and protection of children from infancy to adolescence. The introduction of children to culture, education, values ​​and norms of social life begins in the family environment. For the perfect and harmonious development of children's personalities, they must grow in a family environment in a climate of happiness, love and understanding The formulation of the problem of this study is how the correlation between the implementation of the norms of happy and prosperous small families with learning difficulties in class VIII semester II M.Ts N 1 Banyuwangi. The method used in determining respondents is using proportional random sampling. Data collection methods include: 1) Observation Method; 2) Interview Method; 3) Questionnaire Method; 4) Documentary Method. Analyze data using the tetrachoric correlation statistical method. The results of his research that there is a correlation between the norms of happy and prosperous small families with the learning difficulties of students of class VIII semester II M.Ts N 1 Banyuwangi, the level of relationship obtained by 0.542 lies between 0.400 to 0.600 which means the level of correlation is sufficient.